Difference in Phase Behavior of Suspending Solution and Erythrocyte Concentrate with CRIHBT-115 Cryopreservative During Cooling - Khodko, Aleksey T. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 182.